Evaluation of hardness and surface roughness of two maxillofacial silicones following disinfection - Goiato, Marcelo Coelho [UNESP]; Pesqueira, Aldieris Alves [UNESP]; Santos, Daniela Micheline dos [UNESP]; Dekon, Stefan Fiuza de Carvalho [UNESP] (FapUNIFESP (SciELO), 2009)
The purpose of this study was to evaluate the Shore A hardness and surface roughness of two silicones for maxillofacial prosthetic treatment, under the influence of chemical disinfection and storage. Twenty-eight specimens were obtained, half of which were made of Silastic MDX 4-4210 silicone and, the other half were made of Silastic 732 RTV silicone. The specimens were divided into four groups: Silastic 732 RTV and MDX 4-4210 with disinfection 3 times a week with Efferdent tablets and the same materials without disinfection. The hardness of the materials was analyzed with a Shore A Durometer. The surface roughness was established by a digital portable roughness tester, initially and 2 months after the confection of the specimens. A variance test was applied (2-way ANOVA), followed by Tukey test (the level of significance was set at 1%). The storage time factor statistically influenced (p < 0.01) the materials' properties of hardness and roughness. MDX 4-4210 (28.59 Shore A, 0.789 Ra) presented higher values than Silastic 732 RTV (18.08 Shore A, 0.656 Ra) for both properties. Regarding the disinfection period, there was no significant difference in any of the materials tested. © 2009 Sociedade Brasileira de Pesquisa Odontológica.
Keywords: Disinfection; Hardness; Maxillofacial prosthesis